Inflation Targeting : What is the Meaning of the Bottom of the Band? - Clifton, Eric (IMF Policy Discussion Papers; Policy Discussion Paper ;, 1999)
This paper investigates the meaning of the bottom of target bands in inflation targeting regimes. It is argued that the design of lower limits on target bands, if not done with care, can lead to a lack of transparency, potentially confusing markets about how the authorities will react to a fall in inflation. After first discussing the conceptual issues, the paper then examines the experience with target bands in New Zealand, Israel and Canada and explores how the conceptual issues have played out in practice.